Keengganan membayar zakat menurut perspektif syarak dan perundangan Islam di Malaysia - Azman Ab. Rahman (Penerbit USIM, 2012)
The importance of paying zakat and its punishment from Islamic perspective for person who is reluctant to pay in Malaysia.